Clinicohematological profile of hepatomegaly and or splenomegaly at tertiary care centre - Kikaniya, Nikita K.; Phulgirkar, Pragati P.; Kulkarni, Anjali S.; Gupta, Ishankkumar P. (International Journal of Research in Medical Sciences, 2025)
Background: Hepatomegaly and splenomegaly have varied causes, including infections, hematologic disorders, and malignancies. Timely diagnosis is essential for effective management. This study assessed the etiology, clinical presentation, and hematological profiles of patients with hepatomegaly and/or splenomegaly. Methods: A total of 100 patients undergoing evaluation at a tertiary care hospital from January 2023 to June 2024 were included. Clinical history, examination, hematological tests, and imaging were conducted. Peripheral smear, bone marrow examination, and biochemical tests were performed as needed. Results: The mean age was 33.66±21.45 years, with 53% females. Fatigue was the most common symptom (14%), and fever often accompanied other complaints. Splenomegaly was most frequent (52%), followed by hepatosplenomegaly (30%) and hepatomegaly (18%). Lymphadenopathy was noted in 12% of cases. Mean hematological values included Hb 7.47 gm%, TLC 27,114.28/cm2, PLT 1.41 lac/cm2, MCV 83.82 fl, MCH 29.45 pg, and MCHC 32.92 g%. CML was the most common peripheral smear finding (20%), followed by acute leukemia (8%), hemolytic anemia (5%), and sickle cell disease/thalassemia (4% each). Bone marrow exams also showed CML (20%) and erythroid hyperplasia (11%). Biochemical abnormalities appeared in 10% of patients. Final diagnoses most commonly included CML (19%) and erythroid hyperplasia (11%). Conclusion: Hepatomegaly and splenomegaly present with diverse hematologic profiles. The high prevalence of CML highlights the need for early recognition and intervention, especially in younger and female patients.